Two Different Upper Tract Urological Malignancies on Either Side - W. S. L. De Silva; S. R. De Almeida; G. D. B. J. Karunarathne; A. A. S. Samarathunga; K. M. C. S. Gannoruwa; J. A. S. B. Jayasundara (Case Reports in Urology)
Introduction. The genitourinary system is a recognized site for multiple primary malignant neoplasms even without syndromic anomalies. However, to the best of our knowledge, a case of upper tract urothelial carcinoma (UTUC) with contralateral renal cell carcinoma (RCC) is not reported in surgical literature so far. Case Presentation. A 52-year-old Sri Lankan male patient was found to have a right lower ureteric tumour and a left renal mass together upon investigating for painless visible hematuria. The right ureteric tumour measured 32×22 mm resulting in moderate hydronephrosis and cortical thinning of the right kidney, and the left renal mass measured 43×38 mm involving the lower pole. The biopsy of the right ureteric lesion revealed a high-grade transitional cell carcinoma with focal nested pattern and that of the left renal mass revealed a clear cell carcinoma. Right nephroureterectomy followed by a left partial nephrectomy was performed in six weeks’ interval. The histology of both the resected specimens confirmed the biopsy findings. Discussion. A high-risk upper tract urothelial carcinoma such as the right ureteric tumour of this patient required a nephroureterectomy which makes the management of the contralateral renal cell carcinoma more complex. An adequate functional renal remnant was ensured after offering oncologically sound surgical treatment for both the malignancies of this patient. Conclusion. A UTUC when associated with a contralateral RCC poses challenges in patient management. The preservation of renal excretory function has to be considered as an important determinant in addition to oncologically sound surgical resection when managing complex cases of genitourinary malignancies involving both sides of the upper urinary tract.